The use of the EQ-5D-Y health related quality of life outcome measure in children in the Western Cape, South Africa: psychometric properties, feasibility and usefulness - a longitudinal, analytical study. Issue 1 (January 2017) - Scott, Des; Ferguson, Gillian; Jelsma, Jennifer
Abstract Background The EQ-5D-Y, an outcome measure of Health Related Quality of Life (HRQoL) in children, was developed by an international task team in 2010. The multinational feasibility, reliability and validity study which followed was undertaken with mainly healthy children. The aim of this study was to investigate the psychometric properties of the EQ-5D-Y when used to assess the HRQoL of children with different health states. Method A sample of 224 children between eight and twelve years were grouped according to their health state. The groups included 52 acutely ill children, 67 children with either a chronic health condition or disability and 105 mostly healthy, mainstream school children as a comparator. They were assessed at baseline, at three months and at six months. An analysis of the psychometric properties was performed to assess the reliability, validity and responsiveness of the EQ-5D-Y in the different groups of children. Cohen's kappa, the intraclass correlation coefficient, Pearson Chi-square, Kruskal-Wallis ANOVA and effect size of Wilcoxon Signed-rank test were used to determine the reliability, validity and responsiveness of the instrument. Results The EQ-5D-Y dimensions were found to be reliable on test-retest (kappa varying from 0.365 to 0.653), except for the Usual Activities dimension (kappa 0.199). The Visual Analogue Scale (VAS) was also reliable (ICC = 0.77). Post-hoc analysis indicated that dimensions were able to discriminate between acutely ill and healthy children (all differencesp  < 0.001). The acutely ill children had the lowest ranked VAS (median 50, range 0–100), indicating worst HRQoL and was the only group significantly different from the other three groups (p  < 0.001 in all cases). Convergent validity between all similar EQ-5D-Y and PedsQL, WeeFIM and Faces Pain Scale dimensions was only evident in the acutely ill children. As expected the largest treatment effect was also observed in these children (Wilcoxon Signed-rank test for VAS was 0.43). Six of the nine therapists who took part in the study, found the measure quick and easy to apply, used the information in the management of the child and would continue to use it in future. Conclusions The EQ-5D-Y could be used with confidence as an outcome measure for acutely-ill children, but demonstrated poorer psychometric properties in children with no health condition or chronic conditions. It appears to be feasible and useful to include the EQ-5D-Y in routine assessments of children.